Learners’ Attitude, Motivation, and Habit towards Reading in Second Language - Rahmawati, Istiqomah Nur; Herdawan, Deri (Universitas Islam Negeri Raden Intan Lampung, 2022)
The key in language learning and acquisition is exposure towards said language. The most feasible exposure for English learners in the EFL setting is reading due to practicality, continuity, and suitable sources. Their reading success depends on their attitude, motivation, and habit. This research sought to determine the state of learners’ attitude, motivation, and habit toward reading in English. This qualitative exploratory research was initiated in 2020, taking place at the State Islamic University of Raden Intan Lampung (UIN RIL) and the Indonesian State Maritime Polytechnic (Polimarin). The research population included learners registered in those two universities, with 88 (51.8%) from UIN RIL and 82 (48.2%) from Polimarin selected through quota sampling. A 20 items-questionnaire, complemented by some interview sessions, were used to collect the research data. The collected data were then processed through a model consisting of four stages; data collection, data reduction, data display, and conclusion drawing. The results revealed that the learners showed a generally favourable attitude toward reading in English. This stemmed from good responses shown from all factors of English reading attitude. It should be noted that the previous reading experience factor was the most unfavourable one due to poor start of reading activity. Meanwhile, the learners showed mixed responses regarding their motivation toward reading in English. Two factors, access to materials and English proficiency, were the ones that need further attention, as most learners still lacked in that regard. Ultimately, the learners’ reading habits were still deficient in their native language and even more so in their English reading habits. Keywords: Attitude, Habit, Motivation, Reading, Second Language.